EFFECT OF NITROGEN ENRICHMENT UNDER DIFFERENT CONCENTRATIONS OF SILICATE ON THE RELATIVE GROWTH OF ICE ALGAE IN RESOLUTE PASSAGE, CANADIAN ARCTIC (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - タグチ, サトル /; TAGUCHI, Satoru; SMITH, Ralph E. H. (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper